Bank Mergers - Takeovers and Customer Satisfaction: The Case of a Greek Commercial Bank - Spyros Papathanasiou; Pavlos Mylonas; Dimitris Kenourgios (Int J Financ Econ Trade, 2018)
The aim of this study is to examine the correlation of the service quality dimensions to the overall customer satisfaction in the Greek banking sector, following its restructuring due to the mergers and the takeovers during the current financial crisis period (2009 - 2015), and to analyze in particular the case of Piraeus Bank, the biggest Greek commercial Bank. The research conducted so as the data to be collected, was drawn from a customer sample of the Piraeus Bank and as for the measurements used, are based on the widely accepted SERVQUAL model, as it is proposed by Parasuraman et al. (1988), where the five dimensions of service quality merged: reliability, responsiveness, empathy, assurance and tangibles. According to the results, all service quality dimensions are positively related to the customer satisfaction. The greatest impact, regarding customer satisfaction, was observed most in the dimensions of empathy and reliability. Moreover, it was discovered that a certain type of customer discontent is on the verge of being manifested among the considered bank services.